Health care providers acceptance of default prescribing of TB preventive treatment for people living with HIV in Malawi: a qualitative study - L. M. De Groot; K. Shearer; C. Sambani; E. Kaonga; R. Nyirenda; K. Mbendera; J. E. Golub; C. J. Hoffmann; C. Mulder (BMC, 2024)
Abstract Background Tuberculosis (TB) preventive treatment (TPT) substantially reduces the risk of developing active TB for people living with HIV (PLHIV). We utilized a novel implementation strategy based on choice architecture (CAT) which makes TPT prescribing the default option. Through CAT, health care workers (HCWs) need to "opt-out" when choosing not to prescribe TPT to PLHIV. We assessed the prospective, concurrent, and retrospective acceptability of TPT prescribing among HCWs in Malawi who worked in clinics participating in a cluster randomized trial of the CAT intervention. Methods 28 in-depth semi-structured interviews were conducted with HCWs from control (standard prescribing approach) and intervention (CAT approach) clinics. The CAT approach was facilitated in intervention clinics using a default prescribing module built into the point-of-care HIV Electronic Medical Record (EMR) system. An interview guide for the qualitative CAT assessment was developed based on the theoretical framework of acceptability and on the normalization process theory. Thematic analysis was used to code the data, using NVivo 12 software. Results We identified eight themes belonging to the three chronological constructs of acceptability. HCWs expressed no tension for changing the standard approach to TPT prescribing (prospective acceptability); however, those exposed to CAT described several advantages, including that it served as a reminder to prescribe TPT and routinized TPT prescribing (concurrent acceptability). Some felt that CAT may reduce HCW´s autonomy and might lead to inappropriate TPT prescribing (retrospective acceptability). Conclusions The default prescribing module for TPT has now been incorporated into the point-of-care EMR system nationally in Malawi. This seems to fit the acceptability of the HCWs. Moving forward, it is important to train HCWs on how the EMR can be leveraged to determine who is eligible for TPT and who is not, while acknowledging the autonomy of HCWs.